AdvancED Flash Interface Design - Rosso, Guido; Monnone, Brian; Kemper, Michael (Apress : Imprint: Apress, 2006)
As a competent Flash designer, you're probably comfortable with all of the basics that Flash has to offer. However, you've probably looked at some of the amazing Flash sites on the web and thought, "How'd they do that?" Well, you'll find out in this book. Flash allows users to create some amazing interactive interfaces to interact with rich Internet applications, e-learning systems, and simple web sites. In this book, two of the most talented Flash designers in the world will show you how to use them effectively to create breathtaking visuals for your Flash web sites. You'll also learn how to take advantage of Flash's powerful built-in vector-based drawing tools. The authors discuss general background theory, such as site planning, color theory, and information architecture. They reveal techniques using gradients, layers, lighting and shadowing, 3D objects, animation, and photo editing. Techniques are illustrated and the book concludes with a discussion of usability and final tweaks. There is also a tutorial on testing your work, and exporting and finally publishing it.